KEBERMAKNAAN HIDUP : SEBUAH STUDI KUALITATIF PADA PEREMPUAN DENGAN PENGALAMAN KEKERASAN FISIK DARI SUAMI - Rachmawati, Maya; Herdiana, Ike (Jurnal Abdi Insani, 2024)
In the domestic context, physical violence often affects women and results in deep psychophysical trauma. This research examines the impact of violence on the process of searching for meaning in life among women victims of violence from their husbands by considering resilience and post-traumatic adaptation. This research uses a qualitative approach, applying an instrumental case study design to explore this complex phenomenon. A total of five women who experienced physical violence from their partners and who already had children were selected as participants through snowball and convenience sampling techniques. Qualitative data was collected through in-depth interviews and analyzed using data reduction, data presentation and verification techniques to obtain a holistic and in-depth understanding of the subjective experiences of the participants. The results showed wide variation in the meaningfulness of life felt by participants, which was rooted in their unique experiences. The crisis resulting from violence becomes a starting point in the process of finding meaning, which leads to the formulation of new life goals, redefinition of personal freedom, increased life satisfaction, and a reflective attitude towards death. This research reveals that, despite experiencing a wide range of traumatic conditions, women have the power to find meaning and wholeness in life, offering new insights into resilience and self-healing.